Peran Perbankan Nasional dalam Pembiayaan Sektor Pertanian di Indonesia - nFN Ashari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2009)
EnglishAgricultural sector has a very strategic role in the national development. Nevertheless, the agricultural sector still deals with some problems, e.g. lack of capital for farmers and agricultural business. National banks, theoretically, have a significant potential for agricultural financing because of their core business as the financial intermediary institution. However, the facts show that national banking credit to the agricultural sector is still limited, that is less than 6 percent. This paper aims to review potential, role and the constraint of national banks in financing the agricultural sector. The study shows that the lack of financing in the agricultural sector by national banks caused by high risk in the agricultural sector, complicated term in credit proposal, poor management of agricultural businesses due to its micro-small scale, and limited competence of bank in the field of agricultural finance. The government tries to increase agricultural finance through increasing budget allocation to this sector, improving effectiveness of state budget funds, or formulating an alternative financing scheme in accordance with the characteristics of agriculture. IndonesianSektor pertanian memainkan peran sangat strategis dalam pembangunan nasional. Walaupun demikian, sektor pertanian masih dihadapkan pada beberapa permasalahan, diantaranya kurangnya permodalan petani dan pelaku usaha pertanian. Perbankan nasional, secara teori memiliki potensi besar sebagai pendukung pembiayaan pertanian karena secara legal formal merupakan lembaga intermediasi keuangan. Namun, fakta menunjukkan penyaluran kredit perbankan nasional ke sektor pertanian masih sangat kecil yaitu di bawah 6 persen. Tulisan ini bertujuan melakukan review terhadap potensi dan peran serta berbagai permasalahan yang dihadapi perbankan nasional dalam pembiayaan di sektor pertanian. Hasil studi menunjukkan bahwa minimnya pembiayaan di sektor pertanian oleh perbankan disebabkan beberapa hal, diantaranya: risiko pembiayaan yang tinggi, persyaratan yang ketat dalam pengajuan kredit, kelemahan manajemen usaha pertanian yang umumnya berskala mikro-kecil, serta keterbatasan kompetensi perbankan di bidang pertanian. Pemerintah telah berupaya untuk meningkatkan pembiayaan ke sektor pertanian, diantaranya dengan memperbesar alokasi anggaran ke sektor pertanian, peningkatan efektivitas dana APBN, mendorong perbankan lebih ekpansif dalam pembiayaan pertanian, maupun merumuskan skim pembiayaan alternatif yang sesuai dengan karakteristik pertanian.